2014
DOI: 10.1111/1365-2664.12262
|View full text |Cite
|
Sign up to set email alerts
|

EnvironmentalDNAsurveillance for invertebrate species: advantages and technical limitations to detect invasive crayfishProcambarus clarkiiin freshwater ponds

Abstract: Summary1. The introduction of non-native species is a major threat to biodiversity. While eradication programs of well-established invaders are costly and hazardous for non-target species, the early detection of a non-native species at low density is critical for preventing biological invasions in recipient ecosystems. Recent studies reveal that environmental DNA (eDNA) is a powerful tool for detecting target species in aquatic ecosystems, but these studies focus mostly on fish and amphibians. 2. We examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
283
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(298 citation statements)
references
References 39 publications
(57 reference statements)
13
283
1
1
Order By: Relevance
“…The high-profile invasion of bigheaded carps Hypophthalmichthys molitrix and H. nobilis into waters of the midwestern United States (USA) has also represented a frequent target of eDNA surveillance efforts (Jerde et al 2011;Mahon et al 2013;Turner et al 2014b). Other eDNA surveillance targets in natural waters have included Bluegill Sunfish (Lepomis macrochirus) invading ponds in Japan (Takahara and Minamoto 2013), New Zealand mudsnails (Potamopyrgus antipodarum) in streams of Idaho, USA , PontoCaspian zebra mussels (Dreissena polymorpha) in the midwestern USA (Egan et al 2013), Louisiana crayfish (Procambarus clarkii) in France (Tréguier et al 2014), and African Jewelfish (Hemichromis letourneuxi) and Burmese pythons (Python bivittatus) in Florida, USA's ponds ) and wetlands (Piaggio et al 2014), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The high-profile invasion of bigheaded carps Hypophthalmichthys molitrix and H. nobilis into waters of the midwestern United States (USA) has also represented a frequent target of eDNA surveillance efforts (Jerde et al 2011;Mahon et al 2013;Turner et al 2014b). Other eDNA surveillance targets in natural waters have included Bluegill Sunfish (Lepomis macrochirus) invading ponds in Japan (Takahara and Minamoto 2013), New Zealand mudsnails (Potamopyrgus antipodarum) in streams of Idaho, USA , PontoCaspian zebra mussels (Dreissena polymorpha) in the midwestern USA (Egan et al 2013), Louisiana crayfish (Procambarus clarkii) in France (Tréguier et al 2014), and African Jewelfish (Hemichromis letourneuxi) and Burmese pythons (Python bivittatus) in Florida, USA's ponds ) and wetlands (Piaggio et al 2014), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a number of eDNA studies have shown positive correlations between the eDNA concentrations obtained from quantitative (qPCR) analyses and population abundance indices (Lacoursière-Roussel et al 2016a, 2016bPilliod et al 2013;Takahara et al 2012;Thomsen et al 2012b;Wilcox et al 2013). However, the ability to quantify population abundance using eDNA is still debated (Iversen et al 2015;Roussel et al 2015;Tréguier et al 2014) and the relative sensitivity of both methods is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…With this study, we have complemented research that has compared metabarcoding markers (e.g. : [59,60]), focused on invertebrates [61][62][63] and provided 'ground-truthing' for replicated metabarcoding data by means of morphological data [62][63][64]. We also expand the range of studies investigating the effect of analysis parameters on metabarcoding data sets [35,60,65,66] including the quality of reference data [67,68].…”
Section: Discussionmentioning
confidence: 90%
“…Generally, retrieval of a completely overlapping species inventory between morphological and sequence-based approaches is difficult to achieve due to inherent biases of each approach [61][62][63]. This limitation somewhat constrains comparisons between sequence-based and morphology based taxonomy assignments as performed here.…”
Section: Detecting Highly Abundant and Cryptic Antarctic Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation